Educational performance in Mexico: The Enlace test - Campos Vazquez, Raymundo M.; Urbina Romero, Freddy D. (Estudios Económicos de El Colegio de México, 2011)
This article measures the relationship between a standardized test applied at the national level (Enlace) with bimonthly test results at the classroom level. The results for mathematics imply that a one standard deviation increase in cumulative learning measured with the bimonthly tests increase the Enlace tests scores by 0.84 standard deviations. The result is robust to different estimation methods like quantile regression, fixed effects at the school level and mixed models. Therefore, we conclude that what it is taught in the classroom is reflected in the Enlace test.